Implementing Kahoot Application as Game-Based Learning to Enhance Students’ Vocabulary at SMP Negeri Tiakur - Louisa Sarah Kamanasa; Fredi Meyer; Anaci Alerbitu (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2024)
The integration of Kahoot aims to create an interactive and engaging classroom environment that leverages technology to support English language learning. This study explores the use of the Kahoot app as a game-based learning tool to enhance students’ vocabulary at SMP Negeri Tiakur. The methodology involved three main stages: planning, implementation, and evaluation. The results indicated several positive outcomes: 1) Students were exposed to technological learning tools they had not previously encountered, particularly in English language education. 2) The game-based approach created a lively and enjoyable learning environment, increasing student engagement and participation. 3) Students expressed a strong desire to continue learning English beyond the scheduled activity, highlighting an increase in motivation. 4) The feedback from students suggested a noticeable improvement in their vocabulary acquisition. These findings suggest that Kahoot can be an effective tool for enhancing vocabulary learning in a fun and interactive way, making it a valuable addition to the language learning curriculum. Future research could explore the long-term impacts of such interventions and the potential for similar digital platforms in different educational contexts